Biarticulating two-dimensional computer model of the human patellofemoral joint. - Gill, H; O'Connor, J (1996)
A biarticulating two-dimensional model of the patellofemoral joint has been developed using geometric and force equilibrium constraints to calculate the orientation of the patella about its mediolateral axis. The equations developed from these constraints were solved using an iterative numerical procedure. The model predicts and explains the proximal rolling of the patella on the femur during flexion; it predicts transfer of contact from the trochlea to the femoral condyles at high knee flexion angles. Variation with flexion angle of the patellar mechanism angle and the patellofemoral joint reaction force magnitude agree well with published experimental results.